THE DYNAMICS OF DEVELOPMENT OF HALAL TOURISM DESTINATION IN LOMBOK WEST NUSA TENGGARA - MUAINI MUAINI (Universitas Muhammadiyah Semarang, 2018)
This research aims to uncover and describe the dynamics of the development of halal tourism destination to the change of social culture, economy, education and the role of community leaders. The type ofthis research was used ethnographic research with the data collecting techniques using participant observation,interview, documentation and a field note. The data analysis using inductive. The results showed that the processof the development of halal tourism destination in Lombok, West Nusa Tenggara. The socio-cultural changes ofthe well community that have positive or negative impact. The improvement of the economy of the society insignificant in the halal tourism destination. The level of education that still needs to be improved for thedevelopment of halal tourism destination. The role of community and religious leaders in the development ofhalal tourism destination.Key Words: Dynamics, Development, Halal Tourism Destination.